The Alps: A physical geography, political, and program framework - Nared, Janez; Razpotnik Visković, Nika; Komac, Blaž (Acta geographica Slovenica, 2015)
In order to improve the understanding of the concepts featured in this special issue of Acta geographica Slovenica, this review article presents the Alps as a geographical concept, the Alpine Convention, and the Alpine Space transnational cooperation program. All three categories have a different spatial scope and thus must be clearly defined and distinguished from one another.